Investigating the Antidiabetic Potential of Methanolic Leaf Extracts of Piper umbellatum L. and Persea americana Mill. - Njateng, Guy Sedar Singor; Iqbal, Jamshed (Medical Research and Its Applications Vol. 9, 2024)
Background and Objective: Diabetes increasingly represents a major global concern, especially in developing countries and particularly in Sub-Saharan Africa. According to WHO, the world-wide prevalence of diabetes has almost doubled since 1980, from 4.7% to 8.5% in 2014 in the adult population. The primary objective of this study is to determine the inhibitory activity of methanolic leaf extract of Piper umbellatum and Persea americana (P. americana) (traditionally used in Cameroon against diabetes) on \(α\)-glucosidase, \(β\)-glucosidase, maltase-glucoamylase, aldose reductase and aldehyde reductase activities, enzymes involved in starch digestion or diabetic complications. Methods: The methanol extracts from Piper umbellatum and P. americana were prepared by maceration. To assess the relative efficacy of these extracts, the determination of concentrations that were needed to inhibit 50% of enzyme activity was done, whereas, gas chromatography-mass spectrum was used to identify components from extracts that may be responsible for the activities. Differences in calculated percent inhibition and IC50 values were analyzed using unpaired t-tests as well as one-way ANOVA followed by Tukey-Kramer post-hoc analysis in order to compare data sets. Results: The tested extracts strongly inhibited \(α\)-glucosidase, maltase-glucoamylase, aldose reductase and aldehyde reductase activities with IC50 ranging from (1.07 \(±\) 0.03) to (31.77 \(±\) 1.17) µg/mL. Among the tested extracts, P. americana was the most active against sensitive enzymes (IC50 of 1.07 \(±\) 0.03 to 15.63 \(±\) 1.23). However, none of the extracts showed an interesting inhibitory effect against \(β\)-glucosidase as their percentage inhibitions were less than 16%. From gas chromatography-mass spectrum analysis, 10 and 8 compounds were identified in Piper umbellatum and P. americana extracts respectively, using NIST library 2014. Conclusions: The results of this study provide the scientific credentials for the prospective usage of these plants to treat diabetes. Further work is still needed for the identification of specific anti-hyperglycemic constituents in these extracts and the evaluation of their pharmacological potentials.